The impact of error frequency on errorless and errorful learning of object locations using a novel paradigm. Issue 10 (26th November 2019) - Scheper, Inge; de Bruijn, Ellen R. A.; Bertens, Dirk; Kessels, Roy P. C.; Brazil, Inti A.
ABSTRACT: Errorless learning (EL) is an approach in which errors are eliminated or reduced as much as possible while learning of new information or skills. In contrast, during trial-and-error − or errorful − learning (TEL) errors are not reduced and are often even promoted. There is a complex and conflicting pattern of evidence whether EL or TEL may result in better memory performance. One major confound in the extant literature is that most EL studies have not controlled for the number of errors made during TEL, resulting in a large variability in the amount of errors committed. This variability likely explains why studies on the cognitive underpinnings of EL and TEL have produced mixed findings. In this study, a novel object-location learning task was employed to examine EL and TEL in 30 healthy young adults. The number of errors was systematically manipulated, allowing us to investigate the impact of frequency of errors on learning outcome. The results showed that recall from memory was significantly better during EL. However, the number of errors made during TEL did not influence the performance in young adults. Altogether, our novel paradigm is promising for measuring EL and TEL, allowing for more accurate analyses to understand the impact of error frequency on a person's learning ability and style.